2020
DOI: 10.1038/s41419-020-02745-x
|View full text |Cite
|
Sign up to set email alerts
|

Circ-ADAM9 targeting PTEN and ATG7 promotes autophagy and apoptosis of diabetic endothelial progenitor cells by sponging mir-20a-5p

Abstract: Dysfunction of endothelial progenitor cells (EPCs) is a key factor in vascular complications of diabetes mellitus. Although the roles of microRNAs and circular RNAs in regulating cell functions have been thoroughly studied, their role in regulating autophagy and apoptosis of EPCs remains to be elucidated. This study investigated the roles of mir-20a-5p and its predicted target circ-ADAM9 in EPCs treated with high glucose (30 mM) and in a diabetic mouse hind limb ischemia model. It is found that Mir-20a-5p inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 49 publications
0
30
0
Order By: Relevance
“…We found that in hypoplastic fetal lungs at the canalicular stage, HDAC3 expression was increased compared to normal lungs and rescued to normal levels by AFSC-EV administration (Figure 3F-G). When we investigated the expression of PTEN and GATA4, which are downstream factors in the autophagy pathway and directly or indirectly regulated by the miR-17~92 cluster (34,35), we found that hypoplastic lungs had higher levels than control (Figure 3F-G). Treatment with AFSC-EVs restored PTEN expression back to control levels but had no restorative effect on GATA4 expression (Figure 3F-G).…”
Section: Impaired Fetal Lung Autophagy Is Restored By Members Of the ...mentioning
confidence: 99%
“…We found that in hypoplastic fetal lungs at the canalicular stage, HDAC3 expression was increased compared to normal lungs and rescued to normal levels by AFSC-EV administration (Figure 3F-G). When we investigated the expression of PTEN and GATA4, which are downstream factors in the autophagy pathway and directly or indirectly regulated by the miR-17~92 cluster (34,35), we found that hypoplastic lungs had higher levels than control (Figure 3F-G). Treatment with AFSC-EVs restored PTEN expression back to control levels but had no restorative effect on GATA4 expression (Figure 3F-G).…”
Section: Impaired Fetal Lung Autophagy Is Restored By Members Of the ...mentioning
confidence: 99%
“…uPAR-PI3K/Akt pathway promotes tumor-like behavior of RA FLSs ( 45 ). Also, numerous studies have revealed that the activation of PI3K/Akt/mTOR pathway is involved in ECs angiogenesis ( 46 , 47 ), and p53 can suppress this pathway ( 48 ). Therefore, p53 is considered to be a key checkpoint of angiogenesis ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…While their exact role in AAA formation has not been elucidated, there is evidence connecting some of these miRNAs to EC function. For example, miR-20a inhibits apoptosis of endothelial progenitor cells by targeting PTEN and ATG7 expression, while repressing endothelial migration [ 47 , 48 ]. miRNA-27a is expressed in ECs and promotes angiogenesis by negatively regulating SEMA6A, an anti-angiogenic protein [ 49 ].…”
Section: Epigenetic Modifications In Endothelial Cells In Aaasmentioning
confidence: 99%